Local Antibiotic Delivery Options in Prosthetic Joint Infection - William Steadman; Paul R. Chapman; Michael Schuetz; Beat Schmutz; Andrej Trampuz; Kevin Tetsworth (MDPI AG, 2023)
Prosthetic Joint Infection (PJI) causes significant morbidity and mortality for patients globally. Delivery of antibiotics to the site of infection has potential to improve the treatment outcomes and enhance biofilm eradication. These antibiotics can be delivered using an intra-articular catheter or combined with a carrier substance to enhance pharmacokinetic properties. Carrier options include non-resorbable polymethylmethacrylate (PMMA) bone cement and resorbable calcium sulphate, hydroxyapatite, bioactive glass, and hydrogels. PMMA allows for creation of structural spacers used in multi-stage revision procedures, however it requires subsequent removal and antibiotic compatibility and the levels delivered are variable. Calcium sulphate is the most researched resorbable carrier in PJI, but is associated with wound leakage and hypercalcaemia, and clinical evidence for its effectiveness remains at the early stage. Hydrogels provide a versatile combability with antibiotics and adjustable elution profiles, but clinical usage is currently limited. Novel anti-biofilm therapies include bacteriophages which have been used successfully in small case series.